2018
DOI: 10.1186/s13007-018-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

The elastic modulus for maize stems

Abstract: BackgroundStalk lodging is a serious challenge in the production of maize and sorghum. A comprehensive understanding of lodging will likely require accurate characterizations of the mechanical properties of such plants. One of the most important mechanical properties for structural analysis of bending is the modulus of elasticity. The purpose of this study was to measure the modulus of elasticity of dry, mature maize rind tissues using three different loading modes (bending, compression and tensile), and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…However, previous research has shown the inclusion of these effects to be small and in many cases insignificant. The authors do not believe inclusion of such effects would change the overall conclusions of this paper (Von Forell et al ., 2015; Al-Zube et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown the inclusion of these effects to be small and in many cases insignificant. The authors do not believe inclusion of such effects would change the overall conclusions of this paper (Von Forell et al ., 2015; Al-Zube et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Using the force-displacement response of the specimen from the bending experiments, a flexural stiffness value was calculated for each specimen (Beer et al ). CT-based geometry of the internodal region was then extracted from the internodal region, and used to calculate the longitudinal Young’s modulus of the rind, E’ (Al-Zube et al , 2018). The remaining material properties were calculated based on ratios derived from prior research, tests performed in our lab, and judicious estimates.…”
Section: Methodsmentioning
confidence: 99%
“…We expect to see a distinct relationship between k and span length because diameter influences the ratio of span length to diameter. Due to the layering of the dermal tissues with the internal vasculature, we treated BRs as a “sandwich structured” polymer matrix composite (Al-Zube et al 2018). According to ASTM Standards D726, ideal span length to sample diameter ratio for such composites is 16:1.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical characterization of plant tissues is particularly advantageous for investigating stress response and failure modalities involved in crop damage. Engineering theory and mechanical testing methodologies have been employed to examine the effects of mechanical stress on development in a variety of plants including tomatoes (Coutand et al 2000), trees (Dean et al 2002), barley (Kokubo et al 1989) and maize (Robertson et al 2015a, 2015b, 2016, 2017; Al-Zube et al 2017, 2018; Stubbs et al 2019). In particular, Robertson et al (Robertson et al 2015a) used mechanical testing in maize to investigate the interplay between stalk strength and stalk lodging resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation